Complexity Estimation of Automata Models with Use the Discrete RIV-functions - Anton Epifanov (New Approaches in Engineering Research Vol. 13, 2021)
Methods of the decision of problems of control, synthesis and the analysis of the discrete determined dynamic systems (automatons) use representation of laws of functioning of systems. In phase pictures are systematized and presented the phase trajectories, defining behaviour of systems. The big variety of phase pictures by V. A. Tverdokhlebov is comes to the uniform form - to the symbolical and numerical graphs, which points take places on geometrical curves. At representation of the automaton by geometrical image corresponding automaton mapping will be transformed to the numerical graph with the points, located on geometrical curves. The method of extraction from a geometrical image of laws of functioning of the automaton of sequence of the second coordinates of points, accurate within number of the input signals, offered and developed by V. A. Tverdokhlebov, allows to reduce research of laws of functioning of automatons to research of properties of numerical sequences. In this work is offered the estimation of complexity of laws of functioning of the discrete determined dynamic systems (automatons) on the basis of geometrical representation of laws and use of discrete riv-functions. Is carried out the analysis of more than 10 million discrete riv-functions. As complexity indicators are considered the minimum and maximum number of states at the minimal automaton from the set of automatons, defined by riv-function.